WORKING WITH EDUCATIONAL TEXT AS A MEANS OF DEVELOPING TECHNOLOGICAL LITERACY AMONG STUDENTS - SKALICKA, Katarina (Trends in education, 2010)
One of the aims of engineering courses with a technical orientation is the acquisition and development of technological literacy, which is an important part of general literacy of each pupil. Effective option of developing the technological literacy among students is active working with educational text and application of appropriate methods of work with educational text.
Keywords: educational text - technical literacy - conceptual map.